Analytical study of the management of Baghdad sport clubs according to the comprehensive quality requirements from the point of view of the of the board of directorsmembers - MUNAF , SUHAIR METEAB (International Journal of Psychosocial Rehabilitation, 2020)
The lack of correct and effective practice of these functions leads to the failure of the administrative process and the failure to achieve the desired goals, and we should think about how sports clubs are managed in light Comprehensive quality standards in order to help sports clubs administrations in how to achieve their sporting goals in contributing to preparing the Iraqi society in sports through club management and providing material and human capabilities, and this prompted the researcher to conduct an analytical study for club management in accordance with the comprehensive quality requirements of Baghdad clubs . The research aims to amend the club management scale in accordance with the comprehensive quality requirements of Baghdad clubs, and then identify club management according to the overall quality requirements of the research sample. To achieve the goals of research used the researcher of the curriculum descriptive either research sample consisted of clubs characterized by diversity as well as activities it is a great club and they ( the police, Karkh, army, Zora, Air Force, students, oil, Baghdad Municipality, electricity, industry) by ( 100) member and then the researcher to specify the search scale tool clubs management according to the requirements of the overall quality and then modify it as it became (71) , paragraph (out of 89) and then extracted the scientific basis of honesty and consistency, objectivity , and after it became the standard is ready , the researcher applied to the sample application of the number ( 48) and then the researcher unloaded results processed after obtaining the results concluded the researcher several conclusions , including: lack of use of clubs for considerations of circuit clubs in accordance with the overall quality requirements . Adoption of res talks to learn about the reality of clubs management according to the requirements of the overall quality.